OBSERVATIONS ON THE MATURATION, FECUNDITY AND BREEDING OF THE COMMON CARP, CYPRINUS CARPIO LINNAEUS - Parameswaran, S; Alikunhi, K H; Sukumaran, K K (Indian Journal of Fisheries, 2011)
Observations made on the maturation, fecundity and breeding of theChinese stock of the common carp, Cyprinus carpio var. communis in ponds atCuttack are reported.The fish was found to attain maturity when six to eight months old, themales about two months earlier than the females and at a smaller size. Maturespecimens of both sexes occur throughout the year, being maximum during lateJanuary to March and July to August.